Dual-proxy estimation of Vs30: the case study of the Marche Region (central Italy) - Veronica Gironelli; Tiziano Volatili; Lucia Luzi; Giulio Brunelli; Emanuele Tondi (Journal of Maps)
This study focuses on generating a shear-wave velocity averaged within the uppermost 30 m of the ground surface (Vs30) map for the Marche region (central Italy) using two commonly acknowledged proxies: topographic slope and lithological classification. The analysis is based on a comprehensive dataset of geophysical tests from the Italian seismic microzonation dataset, employed as a training set. Through regression analysis, Vs30 values are modelled as a function of lithology and topographic slope, with a random effect accounting for the combination of these variables. The resulting Vs30 raster map illustrates the spatial distribution of shear-wave velocities across the region, offering a representation of the subsurface seismic characteristics essential for various applications, including local seismic hazard assessment, prediction of seismic ground motion parameters, microzonation mapping, real-time shakemap generation, and seismic design of engineering structures.